THE RELEVANCE OF DIGITAL MARKETING TO HALAL MSMEs IN INCREASING PRODUCT SALES: LITERATURE STUDY - Muhammad Rajab Ardiansyah; Suaidah Suaidah; Maryam Batubara (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Halal Micro, Small, and Medium Enterprises is a business sector that has great potential for economic growth, so halal MSMEs can be a driver of Indonesia's target in terms of becoming a halal center in the world. The development of halal MSMEs must be adapted to the times when the use of technology should be a weapon for halal MSME actors in marketing their products to spread the market to all corners of the world. However, according to data from the Ministry of Cooperatives and SMEs that there are still many MSME actors including Halal MSMEs who have not yet touched on technology in their marketing, this can be seen from the percentage figure which has only reached 13% of MSMEs adopting digital technology. This research design uses a qualitative research approach by conducting a literature study of 15 Google Scholar papers relevant to the research question. The results of this study indicate that digital marketing plays an important role in developing Halal MSMEs, one of which is by using the mixed promotion method (Advertising, Personal Selling, Public Relations, and Direct Marketing).